Those who count: international and national administration of the League’s 1922 census on displaced persons from the Russian Empire - Schacht, Anastassiya (Administory, 2024)
Confronted with dramatic numbers of refugees from the collapsed Russian empire, national bureaucracies and emerging international organisations struggled to provide an adequate response. In 1922, the High Commission for Russian Refugees organized and carried out a census, collecting data on the population and labour potential of refugees. The following article reconstructs this unique experiment in multilateral cooperation between local bureaucracies, humanitarian organisations, and the League. Strategic decisions on the design of the census, dictated by the Commission’s lack of staff and their resorting to experts who were liable for other humanitarian players, affected the census and yielded results hardly usable for effective relief action.
Online veröffentlicht: Januar 2026
Gesehen am 02.02.2026